ANTIOXIDANT DEFENCE SYSTEM INDICES OF RATS TREATED BY SODIUM NITRITE AND THEIR CORRECTION BY L-GLUTAMIC ACID - Salyha, N.О. (World of Medicine and Biology, 2016)
The effect of different doses of L-glutamic acid on activity of antioxidant enzymes and lipid peroxidation products under the influence of sodium nitrite was studied. It was shown that administration of sodium nitrite leads to the activation of free radical processes in the organism of rats and decreased activity of antioxidant enzymes. It was established, that introduction of L-glutamic acid leads to the decrease toxic effects of sodium nitrite.
Keywords: rats; L-glutamic acid; sodium nitrite; antioxidant system; intoxication